Osilodrostat treatment in patients with Cushing’s disease of Asian or non-Asian origin: a pooled analysis of two Phase III randomized trials (LINC 3 and LINC 4) - Akira Shimatsu; Beverly MK Biller; Maria Fleseriu; Rosario Pivonello; Eun Jig Lee; Rattana Leelawattana; Jung Hee Kim; Rama Walia; Yerong Yu; Zhihong Liao; Andrea Piacentini; Alberto M Pedroncelli; et al. (Endocrine Journal)
Cushing’s disease is associated with increased morbidity and mortality. Osilodrostat, a potent oral 11β-hydroxylase inhibitor, provided rapid, sustained mean urinary free cortisol (mUFC) normalization in Cushing’s disease patients in two Phase III studies (LINC 3, NCT02180217; LINC 4, NCT02697734). Here, we evaluate the efficacy and safety of osilodrostat in Cushing’s disease in patients of Asian origin compared with patients of non-Asian origin. Pooled data from LINC 3 and LINC 4 were analyzed. Outcomes were evaluated separately for Asian and non-Asian patients. For the analysis, 210 patients were included; 56 (27%) were of Asian origin. Median (minimum–maximum) osilodrostat dose was 3.8 (1–25) and 7.3 (1–47) mg/day in Asian and non-Asian patients, respectively. mUFC control was achieved at weeks 48 and 72 in 64.3% and 68.1% of Asian and 68.2% and 75.8% of non-Asian patients. Improvements in cardiovascular and metabolic-related parameters, physical manifestations of hypercortisolism, and quality of life were similar in both groups. Most common adverse events (AEs) were adrenal insufficiency (44.6%) in Asian and nausea (45.5%) in non-Asian patients. AEs related to hypocortisolism and pituitary tumor enlargement occurred in more Asian (58.9% and 21.4%) than non-Asian patients (40.3% and 9.1%). Of Asian and non-Asian patients, 23.2% and 13.6%, respectively, discontinued because of AEs. Asian patients with Cushing’s disease generally required numerically lower osilodrostat doses than non-Asian patients to achieve beneficial effects. Hypocortisolism-related AEs were reported in more Asian than non-Asian patients. Together, these findings suggest that Asian patients are more sensitive to osilodrostat than non-Asian patients.